Pharmacoeconomic Analysis of the Diabetes Initiative Program: A Pharmacist-Physician Collaborative Care Model. (December 2013) - Franklin, Brandi E.; Farland, Michelle Z.; Thomas, Jeremy; McFarland, M. Shawn; Ray, Shaunta' M.; Byrd, Debbie C.
Background: Diabetes treatment cost increased 41% from 2007 to 2011. Pharmacists have provided collaborative diabetes management for decades with improvement in disease-related end points. Few have reported economic benefits of pharmacist management of type 2 diabetes.Objective: The purpose was to determine if cost savings associated with hemoglobin A1c (A1C) and systolic blood pressure (SBP) change outweighed programmatic pharmacist-physician collaborative care model costs.Methods: This cost analysis of a 12 month, prospective, multicenter, observational study included English-speaking adults, 18 years or older, with type 2 diabetes mellitus, a life expectancy >1 year, and either a A1C >7%, SBP >130 mm Hg, diastolic blood pressure >80 mm Hg, or low-density lipoprotein concentration >100 mg/dL. Pregnant patients were excluded. Primary analysis outcome was average cost per outcome, ratio of net cost (numerator) and percentage achieving outcomes (denominator). Assessment outcomes included A1C reduction by at least 1% and SBP reduction by at least 5.6 mm Hg.Results: 206 patients were seen by pharmacists during 1612 encounters (mean = 7.8 encounters/patient). Pharmacists spent 983 hours caring for type 2 diabetes patients (mean 3.8 hours/patient). Base case net labor and program costs per patient were −66.77 and 106.81, respectively. Improvement in A1C and SBP yielded 421.01 in cost savings per patient. Labor and program average costs per patient for each outcome achieved were −100.40 and 160.61, respectively.Conclusions: This multisite pharmacist-physician collaboration in diabetes management showed cost savings when assessing pharmacist labor costs alone. Total program costs, including overhead, slightly increased cost of care.